Synthesis and Characterization of Tris(oxazolinyl)borato Copper(II) and Copper(I) Complexes. Issue 2 (3rd February 2021) - Eedugurala, Naresh; Wang, Zhuoran; Kanbur, Uddhav; Ellern, Arkady; Pruski, Marek; Sadow, Aaron D.
Abstract: The reaction of To M Tl (To M =tris(4, 4‐dimethyl‐2‐oxazolinyl)phenylborate) and CuBr2 in benzene at 60 °C provides To M CuBr (1 ) as an entry‐point into tris(oxazolinyl)phenylborato copper chemistry. To M CuO t Bu (2 ) and To M CuOAc (3 ) are prepared by the reactions of To M CuBr with KO t Bu and NaOAc, respectively. To M CuO t Bu is transformed into (To M CuOH)2 (4 ) through hydrolysis. NMR, FT‐IR, and EPR spectroscopies are used to determine the electronic and structural properties of these copper(II) compounds, and the solid‐state structures were characterized by X‐ray crystallography. Reduction of copper is observed upon treatment of To M CuO t Bu with phenylsilane in an attempt to synthesize monomeric copper(II) hydride. To M Cu (5 ) and To M 2 Cu (6 ) were independently synthesized and characterized for comparison. Abstract :